Itaconate as an inflammatory mediator and therapeutic target in cardiovascular medicine - Diotallevi, M; Ayaz, F; Nicol, T; Crabtree, M (Biochemical Society, 2021)
Inflammation is a critical component of cardiovascular disease (CVD), encompassing coronary artery disease (CAD), cerebrovascular events and heart failure and is the leading cause of mortality worldwide. In recent years, metabolism has been placed centrally in the governance of the immune response. Termed immunometabolism, immune cells adapt cellular metabolic pathways to meet demands of activation and thus function. This rewiring influences not only the bioenergetics of the cell but altered metabolites act as signalling molecules to regulate cellular response. In this review, we focus on the TCA cycle derivative, itaconate, as one such metabolite with promising immunomodulatory and therapeutic potential in inflammatory cardiovascular disease.